TREND DESAIN FURNITUR : Pemakai, Nilai Ekonomis, dan Pengembangannya - Herry Puji Harto (Institut Seni Indonesia Yogyakarta, 2014)
The presence of works supportedby adequate capabilities and skills, and supportedby a creative and innovative capabilities, they create works that can meet the demands of thematerial quality, product quality, management quality, and quality of service, and has acomparative advantage, have traits, character and special identity, so that its presence cancompete with other products, and are required to have a new value on creative efforts and aninnovative, so as to reflect the life of the nation that is democratic and accommodatingtowards changes and new developments.Furniture has an important role for the Indonesian economy, but to rely on laborintensiveindustries and is able to give and donate foreign exchange earnings from the exportvalue. Furniture industry highly viscous his Indonesiaan, where the raw materials used bearsalof local natural resources that should be developed., The Indonesian furniture products will bemore competitive and attractive to the world market.Trend furniture design can provide insight into the dynamic neighbor design andfurniture design that can not be separated from the user aspect, sociological relations, marketrelations and cultural trend that developed in the community.Keywords: furniture design trends, economic value, consumer products, design development. Kehadiran karya yang didukung oleh kemampuan dan ketrampilan yang memadai,serta didukung oleh kemampuan yang kreatif dan inovatif, maka tercipta karya yang dapatmemenuhi tuntutan mutu bahan, mutu produk, mutu pengelolaan, dan mutu layanan, danmempunyai keunggulan komparatif, memiliki ciri, karakter dan identitas khusus, sehinggakehadirannya dapat bersaing dengan produk yang lain, dan dituntut memiliki nilai baru atasusaha kreatif dan inovatf, sehingga dapat mencerminkan kehidupan berbangsa dan bernegarayang demokratis dan akomodatif menuju perubahan dan perkembangan baru.Furnitur mempunyai peran yang penting bagi perekonomian Indonesia, selainmengandalkan industri padat karya dan mampu memberikan dan menyumbangkanpenghasilan devisa dari nilai eksport. Industri furnitur yang sangat kental ke-Indonesiaan nya,di mana bahan baku yang digunakan bearsal dari sumber daya alam lokal yang patutdikembangkan., maka produk furnitur Indonesia akan semakin kompetitif dan menarik bagipasar dunia.Trend desain furnitur dapat memberikan pemahaman tetang dinamisasi desain dandesain furnitur yang tidak dapat lepas dari aspek pemakai, relasi sosiologis, hubungan pasardan kecenderungan budaya yang berkembang di masyarakat.Kata kunci: tren desain furnitur, nilai ekonomi, pemakai produk, pengembangan desain.